The Actual AMS Capabilities at the University of Cologne. (3rd July 2017) - Dewald, Alfred
Abstract : Accelerator Mass Spectrometry (AMS) is a technique to measure long-lived radioisotopes with very high sensitivity. The radioisotopes can be of natural origin such as cosmogenic nuclides produced by cosmic rays or of anthropogenic origin such as nuclides produced in nuclear fuel processing or nuclear weapons tests. Since its development in 1977 AMS has revolutionized the field of radionuclide dating. There is nowadays a wide range of applications for AMS in various fields like earth and ocean sciences, archaeology, hydrology, pollution studies, biochemistry, and biomedicine[1] . Throughout the last years, AMS enabled investigations of various astrophysical processes. The detection of supernova-produced 60 Fe in manganese crusts[2], deep-sea reservoirs[3, 4], and microfossils[5, 6] as well as on the surface of the moon[7] constrained a near-by supernovae events approximately 2 million years ago. Moreover, the high sensitivity of the AMS measurements might indicate multiple supernovae events in the near-earth region (<100 parsec) from 3 million to 2 million years ago[4] .